Synthesis and cytotoxicity of new 4-aza-2,3-didehydropodophyllotoxins - Hang, Nguyen Thi Thuy; Yen, Tran Thi; Hoang, Vu Dinh; Quoc Anh, Ngo (Vietnam Journal of Science and Technology, 2022)
Five new 4-aza-2,3-didehydropodophyllotoxins were synthesized by a straightforward multi-component reaction in the hope of finding new structures with interesting anticancer activity. The “one-pot” synthesis process is developed to increase performance as well as minimize the steps involved. The obtained compounds with podophyllotoxin frame have the corresponding yields of 60-83%. Five new 4-aza-2,3-didehydropodophyllotoxins demonstrated comparable cytotoxicity against the Hep-G2, MCF7cell lines with an IC50 value of 52.2 - 261.2 µM with ellipsitine as the positive control.